(untitled) (Acta Scientiarum. Biological Sciences, 2020)
Freshwater shrimps play an important role in many ecological processes since they are epibenthic detritivores but also prey on other invertebrates and are predated by fishes. The knowledge about their biology allow the development of management strategies to improve the use of natural resources by avoiding overfishing and enhancing productivity. Here we evaluated the population structure of the shrimp Macrobrachium amazonicum in the river Rio Grande, upstream of the Ãgua Vermelha hydroelectric dam. They were captured monthly from October 2017 until March 2018, in six sites along the river. The first site was âˆ¿1000 m distant from the dam and the sixth was âˆ¿4000 m distant. A sac-like sieve and traps were used to capture the shrimps. The sieve was dragged three times for 180o. The traps were left by the river margins for six hours. In the laboratory, the shrimps were sexed and measured (carapace length; CL). In total, 6455 individuals were captured: 4499 females (294 breeding), 1445 males, and 217 juveniles. Female mean size was 7.50 ± 3.47 mm, male mean size was 7.44 ± 2.40 mm, and juvenile mean size was 3.24 ± 1.10 mm. The smallest individual was found in site III and it was a juvenile of 1.08 mm. The largest had 20 mm and was found in site II. The smallest breeding female had 3.8 mm CL. The largest individuals were more abundant in the sites near the dam, whereas the smallest were more abundant in the farthest sites. The highest abundance was seen in sites III and IV, and the lowest, in site VI. Unlike males and juveniles, females (both breeding and non-breeding) were more abundant (Anova, p < 0.01) near the dam. By knowing the population structure of M. amazonicum it is possible to understand how they are being affected by the environmental changes caused by the hydroelectric dam